Serum C-Reactive Protein, Erythrocyte Sedimentation Rate, and White Blood Cell Count in Romanov Sheep with Infectious Keratoconjunctivitis - AKGÜL, G.; AKGÜL, M. B.; IRAK, K.; ÇELIK, Ö. Y.; KAHYA DEMIRBILEK, S.; UZABACI, E. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study aimed to evaluate the use of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and white blood cell count (WBC) as markers of the severity of inflammation in the eyes of the Romanov breed sheep with infectious keratoconjunctivitis. A total of 10 Romanov breed sheep between the 1.5 and 2 years of age, including the ones carrying infectious keratoconjunctivitis (G1, n = 5) and healthy ones (G2, n = 5), which were housed under the same care and nutrition conditions were examined, in a sheep breeding enterprise within the boundaries of Siirt province. Staphylococcus aureus sp., Clostridium spp., and Penicillium spp. were detected based on the microscopic morphology of the colonies in swabs collected from the eyes of sick animals. Biochemical tests were performed relevant to the suspected agents while no growth was detected in the swabs of the control group. There was a statistically significant difference in serum CRP and WBC levels between the G1 and G2 groups (p<0.05). No statistically significant difference was found between the values of the other parameters tested. Higher levels of CRP and WBC were determined in sheep having infectious keratoconjunctivitis, are compared to those in healthy animals.